Investigation on Host-Guest Interaction of Cucurbit[8]uril with 1,6-Bis(2-amino-pyridyl)hexane Bromide - Wang, Qi-Sheng; Cong, Hang; Yang, Yu-Zhu; Zhang, Jian-Xing; Tao, Zhu; Feng Xue, Sai; Jiang Zhu, Qian (Asian Journal of Chemistry, 2011)
The host-guest interaction between a designed guest, 1,6-bis(2-amino-pyridyl)hexane bromide (BAPH2+) and cucurbit[8]uril (Q[8], host) has been investigated with electronic absorption spectroscopy and 1H NMR. UV-VIS spectra titration has been employed and a moderate association constants of 1.6 × 104 L/mol has been obtained in a ratio of 1:1. The model of inclusion complex has been confirmed by using 1H NMR.